High Energy And Power Density Asymmetric Supercapacitors Using Electrospun Cobalt Oxide Nanowire Anode - Vidhyadharan, Baiju; Radhiyah, Abd Aziz; Izan Izwan, Misnon; Kumar, Gopinathan M. Anil; Jamil, Ismail; M. M., Yusoff; Rajan, Jose (Elsevier Ltd, 2014)
Electrochemical materials are under rigorous search for building advanced energy storage devices. Herein, supercapacitive properties of highly crystalline and ultrathin cobalt oxide (Co3O4) nanowires (diameter ∼30–60 nm) synthesized using an aqueous polymeric solution based electrospinning process are reported. These nanowire electrodes show a specific capacitance (CS) of ∼1110 F g−1 in 6 M KOH at a current density of 1 A g−1 with coulombic efficiency ∼100%. Asymmetric supercapacitors (ASCs) (CS ∼175 F g−1 at 2 A g−1 galvanostatic cycling) are fabricated using the Co3O4 as anode and commercial activated carbon (AC) as cathode and compared their performance with symmetric electrochemical double layer capacitors (EDLCs) fabricated using AC (CS ∼31 F g−1 at 2 A g−1 galvanostatic cycling). The Co3O4//AC ASCs deliver specific energy densities (ES) of 47.6, 35.4, 20 and 8 Wh kg−1 at specific power densities (PS) 1392, 3500, 7000 and 7400 W kg−1, respectively. The performance of ASCs is much superior to the control EDLCs, which deliver ES of 9.2, 8.9, 8.4 and 6.8 Wh kg−1 at PS 358, 695, 1400 and 3500 W kg−1, respectively. The ASCs show nearly six times higher energy density (∼47.6 Wh kg−1) than EDLC (8.4 Wh kg−1) without compromising its power density (∼1400 W kg−1) at similar galvanostatic cycling conditions (2 A g−1).